Microbial chitosan thin film from palm oil mill effluent for potential application as novel tactile sensor - Hazmi, Alia Tasnim; Ahmad, Farah; Mohd Hatta, Maziati Akmal; Md Ralib @ Md Raghib, Aliza 'Aini (2020)
Piezoelectric is mainly used as energy harvester and as a sensor. Many materials, organic and non-organic, can induced piezoelectricity as long as the crystalline structure is non-centrosymmetric. For renewable and biodegradable material, fungal chitosan is chosen as the piezoelectric material. However, there are many gaps in the fabrication of fungal chitosan thin films that can ensure good mechanical and piezoelectric properties. Thus, the research aim is to fabricate the fungal chitosan thin films and use it to detect the human pulse. The cultivation of Aspergillus oryzae will be done using the palm oil mill effluent (POME) with suitable media composition to optimise the synthesis of chitin. The chitin will then be converted into chitosan through several processes. Using the fungal chitosan, the thin films will be produced and several analyses will be done to study the properties of the films. The chitosan thin film will then be tested as a tactile sensor.